MECHANISM FOR THE APPLICATION OF ISLAMIC BUSINESS ETHICS VALUES IN HOTEL NOOR REVIEWED FROM THE REGULATION OF THE MINISTER OF TOURISM AND CREATIVE ECONOMICS OF THE REPUBLIC OF INDONESIA NO.2 YEAR 2014 ARTICLE 1 VERSE 4 - Tanti Gusmawati (STIESA Press, 2020)
Sharia hotels are hotels with the concept of Islamic syriah, namely hotels that implement sharia in Islamic religion into hotel operations. Not only the label but also must adhere to Islamic rules. Where in this research article focuses on two problem formulations: (1) how the mechanism forwards the values of Islamic business ethics in noor hotel. (2) how is the implementation of the guidelines for the implementation of sharia hotel business in hotels with sharia concept in the hotels Noor Tourism and creative economy Republic of Indonesia No. 2 of 2014? This research approach is qualitative research that produces findings by solving existing problems by presenting, analyzing, interpreting research results. Sources of data in the form of primary data and secondary data with data collection techniques such as observation, interviews, and documentation. The conclusion of this study in the Implementation of Islamic Business Ethics Values and the Implementation of Sharia Hotel Business Implementation Guidelines according to Permen No. 2 of 2014. has been in accordance with and has implemented the values of Islamic Business Ethics, including having implemented the principles of Tawheed, Fairness, Free Will (Freewill), Responsibility (Responsibily), and Ihsan (Benevolance). And Implementation of Sharia Hotel Business Implementation Guidelines according to Permen No. 2 of 2014 namely Products, Services, and Management that have been applied.